2016
DOI: 10.1093/jjco/hyw037
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy and risk of bronchopleural fistula after lung cancer surgery: a systematic meta-analysis of 14 912 patients

Abstract: Objective: Neoadjuvant therapy has been extensively analyzed in studies addressing the risk factors of bronchopleural fistula, but their results vary hugely. Therefore, we conducted this meta-analysis to determine the association between neoadjuvant therapy and risk of bronchopleural fistula in patients undergoing lung cancer surgery. Methods: We searched PubMed and EMBASE to identify the full-text literatures that met our eligibility criteria. Odds ratio with 95% confidence interval served as the summarized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 55 publications
1
40
0
1
Order By: Relevance
“…The incidence of chylothorax in our cohort was 3.2%, which was within the confines of chylothorax rates ranged 2.1–4.0% in the literature [10, 21, 22]. Bronchial fistula was another one fatal complication, revealing a devastating leakage from airways into the pleural space [9, 23]. The most recent evidence-based reviews had showed a bronchial fistula rate ranged 2.4–3.9% following lung cancer surgery [2325].…”
Section: Discussionmentioning
confidence: 79%
“…The incidence of chylothorax in our cohort was 3.2%, which was within the confines of chylothorax rates ranged 2.1–4.0% in the literature [10, 21, 22]. Bronchial fistula was another one fatal complication, revealing a devastating leakage from airways into the pleural space [9, 23]. The most recent evidence-based reviews had showed a bronchial fistula rate ranged 2.4–3.9% following lung cancer surgery [2325].…”
Section: Discussionmentioning
confidence: 79%
“…Various risk factors as neoadjuvant therapy and closure of bronchial stump, had been reported (1,(10)(11)(12). In current study, no case in our cohort administrated neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 52%
“…However, a study performed in our hospital demonstrated that neoadjuvant therapy was independently associated with BPF after pneumonectomy for non-small cell lung cancer (10). Recently reported meta-analysis revealed that both neoadjuvant radiotherapy and chemoradiation therapy significantly increase the bronchopleural fistula risk but neoadjuvant chemotherapy does not (11). Moreover, in study of Asamura et al (1), the incidence of BPF after manual suture (4%) was higher than that after stapler suture (1%), but no significant difference was found.…”
Section: Discussionmentioning
confidence: 89%
“…Li et al (16) reported the results of neoadjuvant chemotherapy in the treatment of locally advanced NSCLC patients, and showed that the surgical resection rate significantly increased to 89.1%, intraoperative blood loss and operation time decreased, and the 3-year survival rate postoperatively significantly increased. Hu et al (17) administered neoadjuvant chemotherapy before radical resection of pulmonary carcinoma.…”
Section: Discussionmentioning
confidence: 99%